The virulence factor regulator and quorum sensing regulate the type I-F CRISPR-Cas mediated horizontal gene transfer in Pseudomonas aeruginosa - Dela Ahator, Stephen; Liu, Yang; Wang, Jianhe; Zhang, Lian-Hui (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa is capable of thriving in diverse environments due to its network of regulatory components for effective response to stress factors. The survival of the bacteria is also dependent on the ability to discriminate between the acquisition of beneficial and non-beneficial genetic materials via horizontal gene transfer (HGT). Thus, bacteria have evolved the CRISPR-Cas adaptive immune system for defense against the deleterious effect of phage infection and HGT. By using the transposon mutagenesis approach, we identified the virulence factor regulator (Vfr) as a key regulator of the type I-F CRISPR-Cas system in P. aeruginosa. We showed that Vfr influences the expression of the CRISPR-Cas system through two signaling pathways in response to changes in calcium levels. Under calcium-rich conditions, Vfr indirectly regulates the CRISPR-Cas system via modulation of the AHL-QS gene expression, which could be vital for defense against phage infection at high cell density. When encountering calcium deficiency, however, Vfr can directly regulate the CRISPR-Cas system via a cAMP-dependent pathway. Furthermore, we provide evidence that mutation of vfr reduces the CRISPR-Cas spacer acquisition and interference of HGT. The results from this study add to the regulatory network of factors controlling the CRISPR-Cas system in response to abiotic factors in the environment. The findings may facilitate the design of effective and reliable phage therapies against P. aeruginosa infections, as targeting Vfr could prevent the development of the CRISPR-Cas mediated phage resistance.